KASHKAR RUBOBI INSTRUCTION TEACHING METHODS IN GRADES 5-7 MUSIC CLUBS (Spectrum Journal of Innovation, Reforms and Development, 2022)
This in the article about the method of teaching the Kashgar rubab instrument in the lessons of music clubs for grades 5-7 complete information you get possible .